Upworthy good people : stories from the best of humanity - Reilich, Gabriel; Knell, Lucia; VanderPloeg, Libby (National Geographic Partners, 2024)
"This heartwarming collection of first-person tales from Upworthy will provide comfort and inspiration to anyone who could use a dose of joy"--